2013
DOI: 10.4028/www.scientific.net/amm.328.758
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Copper Oxide Nanoparticles on the Green Algae: <i>Chlorella pyrenoidosa</i>

Abstract: The toxicity of CuO engineered nanoparticles (ENPs) to chlorella pyrenoidosa was investigated in this study. CuO ENPs inhibited the growth of algal cells significantly, while the Cu ion and CuO bulk particles (BPs) showed lower toxicity than ENPs. The black dots observed in cells using Transmission electron microscopic (TEM) were determined as copper compound by EDS analysis. Cu content in algal cells measured confirmed the Cu internalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…At 96 h, the Cu-MOF-74 had achieved the maximum relative inhibition rate of algal cells (272.74%), but the maximum relative inhibition rate of CuSO 4 $5H 2 O to algae cells was only 39.98% during 0-120 h. It was obviously shown that the suppression ability of Cu-MOF-74 to algae was better than CuSO 4 $5H 2 O, suggesting that Cu-MOF-74 released Cu 2+ was only a part of factor that inhibited the growth of algal cell. Related document has got similar conclusions, Zhang et al 44 found that the inhibition rate of nano-CuO for Chlorella was consistently higher than that of Cu 2+ during experimental culture; Ji et al 45 found that both nano-TiO 2 and nano-ZnO have an impact on the growth of Chlorella, and the inhibition mechanism of nano-ZnO on Chlorella was mainly based on the effect of Zn 2+ and the oxidative damage of algae by ROS etc. Based on the experimental results, it was presumed that the inhibition mechanism of Cu-MOF-74 may have other causes besides the effect of Cu 2+ .…”
Section: Physiological Characterization Of Cyanobacterial Usingmentioning
confidence: 71%
“…At 96 h, the Cu-MOF-74 had achieved the maximum relative inhibition rate of algal cells (272.74%), but the maximum relative inhibition rate of CuSO 4 $5H 2 O to algae cells was only 39.98% during 0-120 h. It was obviously shown that the suppression ability of Cu-MOF-74 to algae was better than CuSO 4 $5H 2 O, suggesting that Cu-MOF-74 released Cu 2+ was only a part of factor that inhibited the growth of algal cell. Related document has got similar conclusions, Zhang et al 44 found that the inhibition rate of nano-CuO for Chlorella was consistently higher than that of Cu 2+ during experimental culture; Ji et al 45 found that both nano-TiO 2 and nano-ZnO have an impact on the growth of Chlorella, and the inhibition mechanism of nano-ZnO on Chlorella was mainly based on the effect of Zn 2+ and the oxidative damage of algae by ROS etc. Based on the experimental results, it was presumed that the inhibition mechanism of Cu-MOF-74 may have other causes besides the effect of Cu 2+ .…”
Section: Physiological Characterization Of Cyanobacterial Usingmentioning
confidence: 71%